Leiomyoma of Broad Ligament Mimicking Ovarian Malignancy– Report of a Unique Case - Mallick, D; Saha, M; Chakrabarti, S; Chakraborty, J (Kathmandu University Medical Journal, 2015)
Tumors of the broad ligament are uncommon. Leiomyoma, which is the commonest female genital neoplasm, is also the most common solid tumor of the broad ligament. Leiomyomas affect 30% of all women of reproductive age but the incidence of broad-ligament leiomyoma is <1%. These benign tumors are usually asymptomatic. A case is being described where a 52 year old presented with gradual abdominal swelling which was clinically and radiologically diagnosed as ovarian malignancy. On abdominal and bimanual palpation a soft cystic mass was noted in the right pelvic region. CA 125 was mildly raised. CEA, CA 19.9 levels were within normal limit. The radiological diagnosis was ovarian cyst with possibility of malignant changes. Staging laparotomy and histopathological examination of the resected specimen revealed a right sided broad ligament leiomyoma with cystic changes. The degenerative changes in the leiomyoma lead to the clinical and radiological diagnostic confusion. Thus, though uncommon, broad ligament leiomyoma should be considered during evaluation of adnexal masses for optimal patient management. The above description of leiomyoma in the broad ligament is a highly unique case and thus deserves appropriate attention. Kathmandu University Medical Journal Vol.12(3) 2014; 219-221